THE RELATIONSHIP BETWEEN DURATION MEMBER OF YOGA EXERCISE AND BODY MASS INDEX TO CARDIORESPIRATORY ENDURANCE AMONG YOUNG ADULT YOGA PRACTITIONERS IN DENPASAR CITY - Dewi, Putu Qonny Trisna; Wibawa, Ari; Purnawati, Susy (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACT Cardiorespiratory endurance is the ability of heart, lungs, and blood capillary to take oxygen and distribute on tissue for metabolism process. Duration of exercise and body mass index is influence to cardiorespiratory endurance of yoga practitioners. The method of this research is cross sectional analytic. This research is measure body mass index and cardiorespiratory endurance with multi stage fitness test on thirty- seven sample. Analysis with Exact Fisher for relationship between duration to cardiorespiratory endurance found the p value was 0.001 and relationship between body mass index to cardiorespiratory endurance with the p value is 0.009. It’s means there are relationship between duration of yoga exercise and body mass index to cardiorespiratory endurance on young adult yoga practitioners in Denpasar City. Key word : Duration, Body Mass Index, Cardio respiratory Endurance, Yoga